2002
DOI: 10.1590/s0100-879x2002000900002
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between paraventricular nucleus and septal area in the control of physiological responses induced by angiotensin II

Abstract: We determined the effects of losartan (40 nmol) and PD 123319 (40 nmol) (both non-peptides and selective antagonists of the AT 1 and AT 2 angiotensin receptors, respectively), and [Sar 1 , Ala 8 ] angiotensin II (ANG II) (40 nmol) (a non-selective peptide antagonist of angiotensin receptors) injected into the paraventricular nucleus (PVN) on the water and salt appetite, diuresis and natriuresis and mean arterial pressure (MAP) induced by administration of 10 nmol of ANG II into the medial septal area (MSA) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…Pilocarpine injected ip produced a copious salivary flow that was potentiated by the previous central injection of L-NAME into the MnPO. Therefore we postulate that the systemic effects of pilocarpine on salivary flow and cardiovascular regulation are influenced by central NO release, in agreement with the results reported by others (16,17). Pilocarpine injected ip decreased the MAP and increased the HR, with an opposite effect when injected into the MnPO, where it acted by increasing salivary flow and blood pressure, with a decrease in HR.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Pilocarpine injected ip produced a copious salivary flow that was potentiated by the previous central injection of L-NAME into the MnPO. Therefore we postulate that the systemic effects of pilocarpine on salivary flow and cardiovascular regulation are influenced by central NO release, in agreement with the results reported by others (16,17). Pilocarpine injected ip decreased the MAP and increased the HR, with an opposite effect when injected into the MnPO, where it acted by increasing salivary flow and blood pressure, with a decrease in HR.…”
Section: Discussionsupporting
confidence: 93%
“…Pilocarpine has been used extensively as the best sialogogue rather than other cholinomimetic agents but produces cardiovascular alterations as side effects. NO plays an important role in the hydromineral and cardiovascular regulation induced by angiotensin (16,17). Different data indicate that the median preoptic nucleus (MnPO) is indeed the target of afferents from osmosensitive and barosensitive systems involved in fluid homeostasis and cardiovascular regulation (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…With the discovery of these multiple subtypes of Ang II receptors, pharmacological studies revealed that the AT 1 subtype mediated both aldosterone [20] and epinephrine [21] release as well as pressor [22, 23], dipsogenic [2224], and sodium appetite [2426] responses to Ang II. The localization of AT 1 receptors in the rat brain regions mediating pressor and dipsogenic actions of Ang II, such as the subfornical organ (SFO), median preoptic nucleus (MnPO), organum vasculosum of the lamina terminalis (OVLT) paraventricular nucleus of the hypothalamus (PVN), nucleus of the solitary tract (NTS), and area postrema [2729] is consistent with this role.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a separate and distinct RAS exists within the mammalian brain is now well established (16). The injection of angiotensin II into the MSA increases sodium excretion (17, 18) and a relationship was determined between the vasopressinergic and angiotensinergic control of water and sodium intake, as well as of medial arterial pressure regulation in the MSA (19, 20).…”
mentioning
confidence: 99%